Pengaruh Pembelajaran Kewirausahaan Dan Teaching Factory Terhadap Intensi Berwirausaha Siswa Kelas XI Akuntansi SMK X - Iswary Amalia; Susilaningsih Susilaningsih (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to: 1) provide empirical evidence of the influence of learning creative and entrepreneurial products on entrepreneurial intentions of students; 2) provide empirical evidence of the influence of the teaching factory on entrepreneurial intentions of students; 3) provide empirical evidence of the influence of creative and entrepreneurial product learning and factory teaching on entrepreneurial intentions of students. This type of research was analytic-descriptive quantitative research. Sampling used proportionate random sampling technique with total sampling of 84 respondents. Data collection in this research used questionnaire. The results is; 1) there is a positive and significant influence between creative product learning and entrepreneurship with entrepreneurial intentions of students as evidenced by the results of the significance value of 0.003 < 0.05; 2) there is a positive and significant influence between teaching factory with entrepreneurial intentions of students as evidenced by the results of the significance value of <0.001 <0.05; 3) there is a positive and significant influence jointly between creative product learning and entrepreneurship and teaching factory for students as evidenced by the results of the significance value of <0.001 < 0.05.